2017
DOI: 10.4269/ajtmh.17-0106
|View full text |Cite
|
Sign up to set email alerts
|

Guillain–Barré Syndrome, Acute Disseminated Encephalomyelitis and Encephalitis Associated with Zika Virus Infection in Brazil: Detection of Viral RNA and Isolation of Virus during Late Infection

Abstract: Zika virus (ZIKV) emerged in Brazil in 2015, which was followed by an increase of Guillain-Barre Syndrome (GBS) cases. We report the epidemiological, clinical, and laboratory findings of the first six neurological cases associated with ZIKV in Brazil seen in a reference neurology hospital in Pernambuco, Brazil. In all cases, ZIKV was detected in serum and/or cerebrospinal fluid (CSF) samples. In this case series, four cases were defined as GBS, one as acute disseminated encephalomyelitis (ADEM) and the other a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 21 publications
3
49
0
Order By: Relevance
“…Compared with urine specimens, a higher proportion of serum specimens had positive ZIKV rRT-PCR results, with the added benefit of also being able to detect anti-ZIKV antibodies. Results are consistent with those reported from Brazil 32 and further suggest that ZIKV RNA persistence was similar among patients with ZIKV disease and those who developed GBS after ZIKV infection. For patients with GBS, adding the median times from antecedent illness to neurologic illness onset (7 days) and from neurologic illness onset to specimen collection (9 days), the time from antecedent illness to specimen collection was roughly 16 days.…”
Section: Discussionsupporting
confidence: 90%
“…Compared with urine specimens, a higher proportion of serum specimens had positive ZIKV rRT-PCR results, with the added benefit of also being able to detect anti-ZIKV antibodies. Results are consistent with those reported from Brazil 32 and further suggest that ZIKV RNA persistence was similar among patients with ZIKV disease and those who developed GBS after ZIKV infection. For patients with GBS, adding the median times from antecedent illness to neurologic illness onset (7 days) and from neurologic illness onset to specimen collection (9 days), the time from antecedent illness to specimen collection was roughly 16 days.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to observations of other viral infections, ZIKV infection may also be related to ADEM. 32,33 The imaging findings described are like those observed in other related causes of ADEM, such as multifocal and asymmetric lesions, affecting the brain and the spinal cord. The clinical course of ADEM-ZIKV cases was very similar to that of the most typical ADEM cases, characterized as a self-limited and monophasic course, appearing weeks after the viral infection.…”
Section: Neurologic Disorders Associated With Zika Virus Infection Insupporting
confidence: 68%
“…A recent study showed ZIKV cases with neurological alterations similar to those found in our study, defined as GBS. In these cases, the viremia appeared to persist for longer than normal (Brito Ferreira et al, 2017 ). While the relationship between Zika fever and GBS still relies solely on epidemiological data, the description of the viral influence toward congenital malformations has become less enigmatic.…”
Section: Discussionmentioning
confidence: 99%